Synthesis and spectroscopic characterization of molybdenum(O) and molybdenum(II) carbonyl benzophenoneazine complexes - Affan, M. A.; Hitam, R.; Shamsuddin, M. (2002)
A chelating 2-methylpyridylbenzophenoneazine ligand has been prepared by the condensation of 2-acetylpyridine with benzophenone hydrazone. Reaction of the ligand with Mo(CO)6 gives 12-methylpyridylbenzophenoneazine)tetracarbonylmolybdenum(0) complex where the ligand is bidentate N, N. Oxidative-addition of the tetracarbonyl complex with 1 mol equivalent of bromine, yields the neutral seven-coordinated dibromotricarbonylmolybdenum(II) azine complex. Treatment of the tetracarbonyl complex with 1 mol equivalent of PPh3 gives the expected tri-carbnonylmolybdenum(O)-azine triphenylphosphine substituted complex